PENGARUH KEPUASAN KERJA TERHADAP KINERJA GURU SMA DAN SMK - Vira Diar Rahmasar; Rahmah Hastuti (Provitae: Jurnal Psikologi Pendidikan, 2023)
The current problem is that many teenagers commit juvenile delinquency to the point that high school and vocational teachers feel tired of handling their students. This study aimed to determine whether job satisfaction impacted the performance of high school teachers. Data collection was carried out in November 2022. This research included 412 public and private high school teachers in Bogor. Data collection was carried out using convenience sampling and purposive sampling. Data collection used the Job Satisfaction Survey (JSS), a job satisfaction measure developed by Paul Spector (1997). Meanwhile, the Individual Work Performance Questionnaire (IWPQ) developed by Koopmans (2014) was used to measure teacher performance. The research data were analyzed using IBM SPSS Statistics version 26. The research results on job satisfaction and teacher performance showed a positive and significant effect on teacher performance. Rewards make higher contribution to improving teacher performance. Employment status and the number of dependents affect performance. Age, length of work, marital status, and the number of dependents affect job satisfaction.